Analisis Mekanisme Produk Tabungan Emas Sebagai Perlindungan Nilai Aset Nasabah di Pegadaian Syariah Lumajang (Lembaga Pengembangan Kinerja Dosen, 2025)
Gold is one of the investment instruments that is quite safe from ancient times to the present, gold has intrinsic value so that its value is not affected by inflation from year to year. In Islam, gold is one of the assets that are recommended to be owned by every individual, as the words of the Prophet Muhammad SAW: